Biotechnology : - Antébi, Elizabeth (MIT Press, 1985)
Biotechnology explains the techniques used (genetic engineering, fermentation, enzymes, cell fusion, monoclonal antibodies, microbiological engineering), the applications (in medicine, food and feed, seeds, plants, energy, pollution, mining and biomaterials), the international economic stakes for investors and industry, and the affect on people's lives in the foreseeable future.